Agreement of the Kato-Katz test established by the WHO with samples fixed with sodium acetate analyzed at 6 months to diagnose intestinal geohelminthes (2015)
The aim of this study was to evaluate the performance of the Kato-Katz test (WHO version) with stool samples from a rural area, fixed with sodium acetate (SAF). The Kato-Katz test was used to compare unfixed samples (conventional test) with the same samples containing SAF fixative at time 0 and at 6 months. The study included stools from 154 subjects.A marginally statistically significant decrease in prevalence was estimated only for hookworm, when comparing unfixed samples versus the SAF fixed samples read at 6 months (. p=. 0.06). A significant reduction in parasite load was found for hookworm (. p less than . 0.01) and Trichuris trichiura (. p less than . 0.01) between the unfixed and the fixed sample read at 6 months, but not for Ascaris lumbricoides (. p=. 0.10). This research suggests that the SAF fixative solution is a good option for transporting samples for diagnosis, especially in rural areas in developing countries. © 2015 Elsevier B.V.